Correlation of stress with anxiety and depression in mexican health personnel caring for covid-19 patients - Medrano Hernández, José Israel; Becerra Hernández, Antonio (Horizonte Sanitario, 2022)
Objective: To determine the correlation between the stress generated in the management of patients with COVID-19 and the development of anxiety and/or depression disorders in the medical staff of Mexican hospitals. Material and methods: This study has a cross-sectional approach to health personnel in COVID hospitals in Mexico. Mexican health personnel who worked in hospitals specially designated for the management of patients with COVID-19 were surveyed during the period from September 1 to November 30 by applying the self-applied scale DASS-21 and PSS- 10 C as a method of assessment. screening, using the online forms function of the Google Docs platform. Results: 314 Mexican health professionals who worked in health institutions during the COVID-19 epidemic were included. Stress evaluated with PSS-10, reported 60.5% moderate stress and 7.3% severe; while with the DASS-21, 15.9% presented moderate stress, 15.3% severe, and 12.1% extremely severe. The prevalence of anxiety was 54.8%, with 18.2% moderate, 7.3% severe, and 21% extremely severe. . The prevalence of depression was 47.1%; being 16.2% moderate, 8% severe and 12.4% extremely severe. The prevalence of anxiety and depression in health workers with stress it was found that the prevalence of anxiety and depression was 77% and 74.7, respectively (p<0.001, χ2). The Odds Ratio was estimated for anxiety and depression in patients with stress, being OR=8.9, CI95% 5.4-15.0 (p<0.001) for anxiety and OR=20.0, CI95% 11.0-36.5 (p<0.001) for depression. Conclusions: In health personnel with stress, the prevalence of anxiety and depression was increased in a proportion of 9 and 20 times the probability, respectively. It is recommended to routinely screen health personnel for the presence of anxiety, depression and stress. Keywords: Anxiety; Depression; Stress